2020
DOI: 10.1007/s10637-020-00941-2
|View full text |Cite
|
Sign up to set email alerts
|

CPBMF65, a synthetic human uridine phosphorylase-1 inhibitor, reduces HepG2 cell proliferation through cell cycle arrest and senescence

Abstract: Hepatocellular carcinoma (HCC) is the most prevalent type of tumor among primary liver tumors and is the second highest cause of cancer-related deaths worldwide. Current therapies are controversial, and more research is needed to identify effective treatments. A new synthetic compound, potassium 5-cyano-4-methyl-6-oxo-1,6-dihydropyridine-2-olate (CPBMF65), is a potent inhibitor of the human uridine phosphorylase-1 (hUP1) enzyme, which controls the cell concentration of uridine (Urd). Urd is a natural pyrimidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
(39 reference statements)
1
4
0
Order By: Relevance
“…Upregulation of UPP1 resulted in an increase in the volume of thyroid tumours, and downregulation of UPP1 suppressed the proliferation of thyroid cancer cell lines 24 . The same results were found for HepG2 cell proliferation subsequent to the use of a synthetic human UPP1 inhibitor 25 . Because the exact mechanism underpinning psoriasis remains unclear, crosstalk between keratinocytes and immunocytes is central to psoriasis.…”
Section: Introductionsupporting
confidence: 60%
See 3 more Smart Citations
“…Upregulation of UPP1 resulted in an increase in the volume of thyroid tumours, and downregulation of UPP1 suppressed the proliferation of thyroid cancer cell lines 24 . The same results were found for HepG2 cell proliferation subsequent to the use of a synthetic human UPP1 inhibitor 25 . Because the exact mechanism underpinning psoriasis remains unclear, crosstalk between keratinocytes and immunocytes is central to psoriasis.…”
Section: Introductionsupporting
confidence: 60%
“…According to previous studies, excessive keratinocyte proliferation contributes to the pathogenesis of psoriasis 1 . Moreover, UPP1 was found to be active in cancer cell lines and to facilitate cell proliferation 25 . These observations suggested a potential correlation between UPP1 and psoriasis.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…In addition, CB-839 upregulated the expression of UPP1 in various transplantation tumor models, strengthening the inhibitory effect of 5-FU on PIK3CA-mutant colorectal cancer 63 . da Silva EFG et al demonstrated for the first time the ability of CPBMF65 to inhibit the proliferation of HepG2 cells by blocking the cell cycle and promoting cellular senescence 64 . Based on its in vitro antitumor activity and low toxicity in normal cells, CPBMF65 may be a candidate for future in vivo therapeutic studies in hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%